Dominant collagen XII mutations cause a distal myopathy. Issue 10 (11th September 2019) - Mohassel, Payam; Liewluck, Teerin; Hu, Ying; Ezzo, Daniel; Ogata, Tracy; Saade, Dimah; Neuhaus, Sarah; Bolduc, Véronique; Zou, Yaqun; Donkervoort, Sandra; Medne, Livija; Sumner, Charlotte J.; et al.
Abstract: Objective: To characterize the natural history and clinical features of myopathies caused by mono‐allelic, dominantly acting pathogenic variants in COL12A1. Methods: Patients with dominant COL12A1 ‐related myopathies were characterized by history and clinical examination, muscle imaging, and genetic analysis. Pathogenicity of the variants was assessed by immunostaining patient‐derived dermal fibroblast cultures for collagen XII. Results: Four independent families with childhood‐onset weakness due to novel, dominantly acting pathogenic variants in COL12A1 were identified. Adult patients exhibited distal‐predominant weakness. Three families carried dominantly acting glycine missense variants, and one family had a heterozygous, intragenic, in‐frame deletion of exon 52 of COL12A1 . All pathogenic variants resulted in increased intracellular retention of collagen XII in patient‐derived fibroblasts as well as loss of extracellular, fibrillar collagen XII deposition. Since haploinsufficiency for COL12A1 is largely clinically asymptomatic, we designed and evaluated small interfering RNAs (siRNAs) that specifically target the mutant allele containing the exon 52 deletion. Immunostaining of the patient fibroblasts treated with the siRNA showed a near complete correction of collagen XII staining patterns. Interpretation: This study characterizes a distal myopathy phenotype in adults with dominant COL12A1 pathogenic variants, further defining the phenotypic spectrum and natural history of COL12A1 ‐related myopathies. This work also provides proof of concept of a precision medicine treatment approach by proposing and validating allele‐specific knockdown using siRNAs specifically designed to target a patient's dominant COL12A1 disease allele.